METHODOLOGY FOR RESPONSE SURFACES APPLIED IN METALS MACHINING - ACHCAR, Jorge Alberto; FARIA, Ricardo Felipe; PIRATELLI, Cláudio Luis (Brazilian Journal of Biometrics, 2016)
In this paper we present the optimization of machining parameters in manufacturing (ANSI) 304 stainless steel devices in an industry of medical / dental instrumental devices in the city of Ribeirão Preto, SP - Brazil. A first objective of this study is to analyze the possible factors affecting the machining process in terms of quantity of parts produced and manufacturing time of each unit. There is also interest in discovering the important covariates that affect the total time (durability) of the life of the cutting tool. Multiple linear regression has been used considering a selected sample of size 28 based on a 7x4 factorial design. With the factors identified, the goal was to determine the optimal values that maximize the quantity produced and minimize manufacturing time using standard canonical response surface methodology and also exploratory "steepest ascent" techniques.